2004
DOI: 10.1111/j.1439-0272.2004.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paternal cigarette smoking on testicular function, sperm fertilizing capacity, embryonic development, and blastocyst capacity for implantation in rats

Abstract: We evaluated the effects of paternal smoking on testicular function, sperm fertilizing capacity, embryonic development, and blastocyst capacity for implantation. Rats of group A were exposed to cigarette smoke for 10 weeks. Rats of group B were exposed to the smoke of incense sticks for 10 weeks. Rats of group C served as a control group. Rats of group D were exposed to cigarette smoke for 7 weeks only. Experimental period was 10 weeks in all groups. At the end of the experimental period serum testosterone res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 53 publications
5
67
0
1
Order By: Relevance
“…Our results with MS smoke confirm previous findings in rats that showed significant decreases in fertilization and embryonic cleavage (Kapawa et al, 2004). However, the effects observed in the current study with lower exposure levels (cotinine level of 95.4 ± 23.5 ng/mL vs.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Our results with MS smoke confirm previous findings in rats that showed significant decreases in fertilization and embryonic cleavage (Kapawa et al, 2004). However, the effects observed in the current study with lower exposure levels (cotinine level of 95.4 ± 23.5 ng/mL vs.…”
Section: Discussionsupporting
confidence: 42%
“…Delayed early embryonic development has been associated with the generation of blastocysts with lowered capacity for implantation and reduced numbers of live offspring (Kapawa et al, 2004). Our results suggest that paternal exposure to MS smoke alters sperm genetic or epigenetic factors that affect the developmental capacity of the fertilized embryo.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been demonstrated that oocytes injected with spermatozoa with high motility have a significantly higher chance of reaching the blastocyst stage [30,43]. It has also been reported that paternal cigarette smoke exposure affects the embryonic implantation ability [21]. However, the results of the above-mentioned studies should be interpreted with caution because some of these results were based on the continued culture of embryos that were considered unsuitable for transfer or cryopreservation on day three of development.…”
Section: Discussionmentioning
confidence: 99%
“…Kapawa et al (22) detected that exposed to tobacco smoke for 10 weeks decreased in the percentage of motile sperm.…”
Section: Discussionmentioning
confidence: 99%